2018
DOI: 10.1038/s41598-018-35201-0
|View full text |Cite
|
Sign up to set email alerts
|

Energy/Electron Transfer Switch for Controlling Optical Properties of Silicon Quantum Dots

Abstract: The superior optical properties of Silicon Quantum Dots (SQDs) have made them of increasing interest for a variety of biological and opto-electronic applications. The surface functionalization of the SQDs with aromatic ligands plays a key role in controlling their optical properties due to the interaction of the ligands with the electronic wave function of SQDs. However, there is limited reports in literature describing the impact of spacer groups connecting the aromatic chromophore to SQDs on the optical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 60 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…A water-soluble SQD-N-propylurea-PDI assembly showed efficiency in fluorescent imaging embryonic-kidney HEK293 cells and human-bone cancerous U2OS cells. These SQD nanoparticles with a size of about 1.6 nm were constructed by heating PTCDA with 3-aminopropyl)triethoxysilane, which was previously reduced by trisodium citrate dihydrate in glycerol [ 97 ]. This Urea-SQD-PDI was sensitive to pH changes with a decrease in the emission intensity collected at 480 nm over a pH range of 2.6–4.…”
Section: Perylenediimide (Pdi)-based Systems For Bioimaging Ptt and Pdtmentioning
confidence: 99%
“…A water-soluble SQD-N-propylurea-PDI assembly showed efficiency in fluorescent imaging embryonic-kidney HEK293 cells and human-bone cancerous U2OS cells. These SQD nanoparticles with a size of about 1.6 nm were constructed by heating PTCDA with 3-aminopropyl)triethoxysilane, which was previously reduced by trisodium citrate dihydrate in glycerol [ 97 ]. This Urea-SQD-PDI was sensitive to pH changes with a decrease in the emission intensity collected at 480 nm over a pH range of 2.6–4.…”
Section: Perylenediimide (Pdi)-based Systems For Bioimaging Ptt and Pdtmentioning
confidence: 99%
“…105 PL-Emission from 2P absorption demonstrated that dye-functionalized SiQDs could be used as a bioimaging probe. 27,131,132 Fig. 13 shows PL images of zebrafish that have been treated with S-SiQD.…”
Section: View Article Onlinementioning
confidence: 99%
“…Contrary to our previous discussion, it turns out that the PLQY measurements deviate from quantum confinement theory for the ligands that are not derived from alkyl groups. 37,[76][77][78] Reports from various authors 9,27,28,[53][54][55]62,74,[79][80][81] indicate that the attachment of more electronegative ligands causes a shift in the emission of SiQDs. 82 For example, SiQDs attached to carbazole (Ca) shows a blue emission shift from l max 780 nm for an average f 3.0 nm diameter of R-SiQDs to l max 530 nm.…”
Section: A Introductionmentioning
confidence: 99%
“…To our knowledge, there has only been one proof-of-concept study on FRET-based sensing 38 and the few in-depth photophysical studies have not addressed pairing with molecular dyes. 39–41…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there has only been one proof-of-concept study on FRET-based sensing 38 and the few in-depth photophysical studies have not addressed pairing with molecular dyes. [39][40][41] Here, we report a detailed and multifaceted study of energy transfer (ET) between aqueous SiNC donors and dye acceptors. The PL of the SiNCs was first characterized using spectroelectrophoresis and time-gated spectroscopy to resolve heterogeneity in the nanocrystal size.…”
Section: Introductionmentioning
confidence: 99%